Um estudo sobre dinâmica familiar de crianças com dificuldades de aprendizagem em fase de alfabetização - Coelho, Helenita Meyer de Macedo (2004)
The objective of this work is to understand the dynamics of families whose children have learning difficulties, during the period of literacy. In theoretical grounding, we adopt a systemic approach, as much to define family dynamics as to discuss difficulties of learning. To get our objective, during the investigation, we count on five mothers, one father, one (that shows up for interwiew next to his wife), two teachers and two school coordinatiors from two schools where the children study; and five children, this way consisting of five cases or five family sistems. To the children, we use the technique of Drawings of the Family with Estory (DF-E). To the fathers, the teachers and the school coordinatiors, we use the semi- strutured interwiew. Our analysis occur on two different moments: one analysis case by case and, on second moment, the general analysis of the cases. The results indicate a family dynamics that focus itself in children, with concern to get their well-being and it values the study as to achieve success in life. By other side, we check the difficult on differentiation/individual process that concerns the children, translated though mechanisms like a superprotection, excess of care, fragile tough excess of control and strict tough, identifications and comparisons. Our study show also the false knowledge that are behind the secrecies and myths, the double messages, the family commands, that become structural elements of family dynamics. This way, these elements of family dynamics. This way these elements work like something that inhibits the character in his own exploration, taking ourselves to reflect about its influence on learning. The purpose of this study is to offer subsidies to parents and profissional workers that deal with children that have learning difficulties and their families, emphasizing the importance of family context on full development of individual